2016
DOI: 10.5539/ies.v9n12p194
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Psychological Well-Being and Job Satisfaction Levels in Different Occupations

Abstract: The purpose of this research was to investigate the relationship between job satisfaction and psychological well-being levels of different occupational employees (education, security, health, justice, worker, engineer, and religious official) carrying on their duties in different institutions and organizations in a mid-scale provincial center of Eastern Anatolian region in Turkey. Furthermore, the research also discussed the differentiation between psychological well-being and job satisfaction in terms of occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
3
1
4
Order By: Relevance
“…Career is a crucial element in one's life and has an impact on an individual's welfare. This proposition has been supported by empirical researches indicating a close relationship between career satisfaction and wellbeing [23][24][25]. The happenstance learning theory holds that there should not be a distinction between career and personal counselling inasmuch as our career affects our personal life and vice versa.…”
Section: Planned Happenstance and Wellbeingmentioning
confidence: 86%
“…Career is a crucial element in one's life and has an impact on an individual's welfare. This proposition has been supported by empirical researches indicating a close relationship between career satisfaction and wellbeing [23][24][25]. The happenstance learning theory holds that there should not be a distinction between career and personal counselling inasmuch as our career affects our personal life and vice versa.…”
Section: Planned Happenstance and Wellbeingmentioning
confidence: 86%
“…Sisask et al (2014) confirmed that higher the PWB among school teachers, higher their readiness to help students with mental health problems. In an analysis of relationship between job satisfaction and PWB across different types of employees including teachers (Isgor & Haspolat, 2016), it was found that the two variables were positively correlated (r = 0.49, p < .01). Among teachers who participated in a study in Hong Kong (Mcinerney et al, 2014), it was established that PWB was associated with organisational and occupational commitment.…”
Section: Psychological Well-being Among Teachersmentioning
confidence: 99%
“…Modal psikologi merupakan suatu hal yang penting yang harus dimiliki baik oleh seorang pemimpin maupun oleh pegawainya dalam pelaksanaan serta koordinasi dalam pekerjaan, modal psikologi yang baik akan berpengaruh terhadap kepemimpinan seorang atasan terhadap bawahannya (Zubair & Kamal, 2017) (Isgor & Haspolat, 2016), dari pernyataan tersebut dapat diambil kesimpulan bahwa seorang pegawai yang memiliki psychological well-being yang baik maka akan berdampak pada kepuasan kerja yang lebih baik dalam keseharian pekerjaannya. Pada penelitian yang dilakukan oleh (Wright & Cropanzano, 2000) ditemukan bahwa peran dari psychological well-being dan kepuasan kerja memiliki hubungan yang positif dalam meningkatkan kinerja pegawai.…”
Section: Empowering Leadership Style Dan Modal Psikologiunclassified